Race and the Responsibility to Abide by the Norms of Unchosen and Unjust Social Roles. (9th March 2019) - Kisolo-Ssonko, Joseph
Abstract: Charles Mills claims that there are specific "civic and political duties" which individuals have a responsibility to fulfil because of the racial social roles they occupy. However, even those generally sympathetic to Role Ethics resist the idea that such nonvoluntary and morally problematic roles could ground genuine normativity. I argue that we should take the felt normativity of nonideal social roles seriously. Further, I argue that we should agree with Mills that one's race constitutes a social role with normative force. However, I claim that Mills is wrong to seek to ground this normativity in an actual social contract (the "racial contract") and I argue instead that Margaret Gilbert's account of joint commitment, and its accompanying notion of collective intentionality, can be developed so as to provide a more promising proposal. I conclude that the responsibility to abide by the norms in question is better understood as grounded in the individual role holder's involvement in the collective intentionality of the relevant racial class.